2023
DOI: 10.1007/s10120-023-01364-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of PD-1 positive CD8 T-cells in gastric cancer

Abstract: Background We evaluated the relevance of PD-1+CD8+ T-cells in gastric cancer (GC) including prognostic significance, association with chemotherapy and immunotherapy sensitivity and correlations with the tumor microenvironment (TME). Methods Discovery cohort: GC samples were evaluated for AE1/3, CD8, PD-1, Ki-67 and Granzyme-B expression with fluorescence-based multiplex immunohistochemistry (mIHC). Validation cohorts: we analyzed bulk RNAseq GC datasets fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…What is more, PD‐1+ CD8 T cells that express Ki67 have been reported a predictive character of proliferating T cells for the response to anti‐PD‐1 therapy in melanoma and NSCLC 102,103 . This result is consistent with a most recent study from discovery cohort of 350 GCs patients, indicating that increased PD‐1+CD8+ T‐cells were statistically prognostic for OS and correlated with Granzyme‐B+ and proliferative Ki‐67+ activity with immunotherapy 104 . Additionally, According to Hashemi et al., 105 stromal CD8 + TILs could be powerful predictors of better outcomes in NSCLC patients previously treated with anti‐PD‐1 therapy, based on real‐world study.…”
Section: Circulating Immune Cells In Antitumor Immunotherapysupporting
confidence: 88%
“…What is more, PD‐1+ CD8 T cells that express Ki67 have been reported a predictive character of proliferating T cells for the response to anti‐PD‐1 therapy in melanoma and NSCLC 102,103 . This result is consistent with a most recent study from discovery cohort of 350 GCs patients, indicating that increased PD‐1+CD8+ T‐cells were statistically prognostic for OS and correlated with Granzyme‐B+ and proliferative Ki‐67+ activity with immunotherapy 104 . Additionally, According to Hashemi et al., 105 stromal CD8 + TILs could be powerful predictors of better outcomes in NSCLC patients previously treated with anti‐PD‐1 therapy, based on real‐world study.…”
Section: Circulating Immune Cells In Antitumor Immunotherapysupporting
confidence: 88%
“…However, there was a significant difference in the DOR, and the significant difference in survival was largely attributed to the differences among responders. Similarly, Choo et al showed that in 58 patients who received first-line platinum and fluoropyrimidine doublet as palliative treatment, patients with high PDCD1 and CD8A expression had longer PFS and OS, albeit not related to the response [23,49]. This suggests that even if the cytotoxic effect of chemotherapy provides a similar reduction effect on the tumor, other factors beyond cytotoxicity contribute to the durable effect of chemotherapy, which may be associated with increased tumor-specific immunity, represented by high circulating PD-1 + CD8 + T cells levels on day 7.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have been conducted to elucidate the prognostic significance of PD-1 + CD8 + T cells present in the TME of GC; however, their results are conflicting [11,17,23,47]. Choo et al analyzed tissues from 350 patients with stage I-IV GC and found a strong correlation between PD-1 + CD8 + tumor-infiltrating lymphocytes (TILs) and the expression of Ki-67 and Granzyme B.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations